2018
DOI: 10.47203/ijch.2018.v30i01.011
|View full text |Cite
|
Sign up to set email alerts
|

Underweight as a Risk Factor for Nutritional Anaemia – A Cross-sectional Study among Undergraduate Students of a Medical College of Haryana

Abstract: Background: Nutritional anaemia is the most common nutritional problem worldwide. Underweight and anaemia are associated and together constitute a serious problem in developing countries like India. Aim & Objectives: To estimate the prevalence of anaemia among medical students and determine its association with their body mass index (BMI). Material & Methods: Hemoglobin estimation was done in 140 MBBS students and anaemia status was determined by WHO criteria for anaemia. BMI was calculated and interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…High Hb content recorded for overweight participants may probably be due to the nutritional status of these groups such as intake of high iron foods and also due to over-nutrition. The study done by Khan et al ( 42 , 43 ) also showed a statistically significant positive correlation of BMI with haemoglobin. Contrary to this, Abro et al ( 45 ) also found a negative correlation between Hb content and BMI among adolescents.…”
Section: Discussionmentioning
confidence: 71%
“…High Hb content recorded for overweight participants may probably be due to the nutritional status of these groups such as intake of high iron foods and also due to over-nutrition. The study done by Khan et al ( 42 , 43 ) also showed a statistically significant positive correlation of BMI with haemoglobin. Contrary to this, Abro et al ( 45 ) also found a negative correlation between Hb content and BMI among adolescents.…”
Section: Discussionmentioning
confidence: 71%
“…There is a significant association between nutritional status and anemia, as anemia is more prevalent among underweight students than expected and overweight students. However, the severity of anemia is not associated with body mass index (Khan et al, 2018). From Table 5 above, we can observe that only 36% had a normal BMI.…”
Section: Resultsmentioning
confidence: 87%
“…A similar finding was reported by Kamble et al (2021) in Delhi, Varma and Baniya. (2022) in Rajasthan, Khan et al, (2018) in Haryana that the prevalence of anaemia is higher among those under adolescents group [13,23,27].…”
Section: Discussionmentioning
confidence: 96%